A novel faster failure detection strategy for link connectivity using Hello messaging in mobile ad hoc networks. (25th September 2019) - Naushad, Alamgir; Abbas, Ghulam; Abbas, Ziaul Haq; Jiao, Lei
Faster failure detection is one of the main steps responsible for efficient link connectivity in mobile ad hoc networks (MANETs). Under a random behaviour of network nodes and link/node failure, there must be a unified approach to describe an adequate Hello messaging strategy for link connectivity in MANETs. In order to tackle this issue, we present a strategy for achieving faster failure detection, and derive algorithmic attributes of the proposed strategy on the basis of multiple parameters of interest after modelling it as a Markov process. We also present novel algorithms to minimise the biggest chunk of delay incurred as a result of link re-connectivity and, thus, improve network connectivity in MANETs. Simulation and analytical results indicate efficacy of the proposed strategy in achieving faster failure detection and efficient link re-connectivity.